Relevant aspects in crimes where being a public official or servant aggravates punishment, and in others it provides a special degree of protection - Larico Portugal, Jorge Josmell (2022)
The prerogative of being a public official or servant entails a responsibility to carry out a correct public administration, on many occasions various criminal types consider having the status of a state worker an aggravating situation; and, in others, they provide them with a degree of protection if they are passive subjects of a crime. In this article we will address a definition from a national and international perspective of the civil servant and public servant. In addition, we will conceptualize and treat the crime of embezzlement by extension as it is a criminal type siu generis in its kind. In this sense, this article aims to analyze the various criminal types provided for in our Penal Code where being an official and public servant constitutes a circumstance of greater aggravation of the sentence and in others where it stands as a special protection or guarantee, explaining the reason why which either aggravates the sentence or protects the public official. After that, we will conclude that the special condition of being a public official has its benefits within the framework of criminal law because it gives you greater protection; in but, it could also harm as an aggravating circumstance and would increase the penalty.